Womenâ€™s Stereotypes in â€œPretty Girlâ€ Song Lyrics: A Critical Discourse Analysis Study - Aprilia, Fitria; Neisya, Neisya (Institut Agama Islam Negeri (IAIN) Curup, 2022)
One of the components in music or song which can be used as an access to the image of women is song lyrics. Woman image presents mental, spiritual, and daily behavior expression by women in many aspects; physical and psychological as women's self-image, family as well as community traits as part of social images. Through language written as song lyrics, a discourse can be expressed according to what the songwriter feels and thinks. The objective of this study is to find out how the image of women which becomes a stereotype is represented in the lyrics of the song